Working sober : the transformation of an occupational drinking culture - Sonnenstuhl, William J., 1946- (ILR, 1996)
Americans assume that workers do not drink on the job and that, if they do, it is because they suffer from alcoholism rather than because they are conforming to occupational expectations. William J. Sonnenstuhl disagrees. He contends that some occupational cultures encourage heavy drinking. Moreover, his research suggests that the sense of community which motivates drinking can also sometimes inspire workers to break the pattern and work sober.